Magnitude and Reliability of Velocity and Power Variables During Deadlifts Performed With and Without Lifting Straps - Jukic, Ivan; García-Ramos, Amador; Malecek, Jan; Omcirk, Dan; Tufano, James J (Journal of strength and conditioning research, 2022)
Jukic, I, García-Ramos, A, Malecek, J, Omcirk, D, and Tufano, JJ. Magnitude and reliability of velocity and power variables during deadlifts performed with and without lifting straps. J Strength Cond Res 36(5): 1177-1184, 2022-This study aimed to compare the magnitude and reliability of mean velocity (MV), peak velocity (PV), mean power (MP), and peak power (PP) between deadlifts performed with (DLw) and without (DLn) lifting straps. Sixteen resistance-trained men performed a DLn 1-repetition maximum (1RM) session followed by 4 experimental sessions (2 with each deadlift variant in a randomized order). Each experimental session comprised lifts at 20, 40, 60, and 80% of the DLn 1RM. No significant differences were found between DLw and DLn for MV, MP, PV, and PP at any load (p = 0.309-1.00; g = 0.00-0.19). All mechanical variables showed an acceptable reliability for both deadlift conditions at each relative load (coefficient of variation [CV] <8%; intraclass correlation coefficient [ICC] > 0.70; g < 0.5) with the only exception of MV at 60% 1RM for DLw (ICC = 0.62) and at 40% 1RM for DLn (ICC = 0.65). Furthermore, MV and PV generally had lower within-subject CV (CV = 3.56-5.86%) than MP and PP (CV = 3.82-8.05%) during both deadlift conditions. Our findings suggest that sport professionals might not need to consider implementing lifting straps with the aim to maximize velocity and power outputs with submaximal loads in a deadlift exercise. Because all mechanical variables measured showed an acceptable level of reliability for both DLw and DLn, they can all be used to track changes in performance during the deadlift exercise. However, velocity variables were slightly more consistent (lower CV), which makes them more appropriate to track DLw and DLn performance changes.
Keywords: svalová síla; Reproducibility of Results; Muscle Strength; Male; vzpírání; lidé; mužské pohlaví; cvičení; odporový trénink; Weight Lifting; Humans; Exercise; reprodukovatelnost výsledků; Resistance Training